Surgery and adjuvant radiotherapy for unilateral ductal carcinoma in situ (DCIS) in women aged over 70 years: A population based cohort study. Issue 8 (August 2019) - Jauhari, Yasmin; Gannon, Melissa Ruth; Tsang, Carmen; Horgan, Kieran; Dodwell, David; Clements, Karen; Medina, Jibby; Tang, Sarah; Pettengell, Ruth; Cromwell, David Alan
Abstract: Background: There is little clinical evidence to guide treatment decisions for ductal carcinoma in situ (DCIS) in older women. This study evaluated how the management of DCIS in women aged 70 or more compared with women aged 50–69 in England and Wales. Method: The study identified women aged ≥50 years with new unilateral DCIS diagnosed between 2014 and 2016 from linked cancer registration and routine hospital datasets for England and Wales. Rates of surgery and adjuvant radiotherapy were examined by age, deprivation, fitness measures (comorbidity and frailty), method of presentation and tumour grade using multilevel logistic regression. Results: 12, 716 women were diagnosed with unilateral DCIS between 2014 and 2016, of whom 2, 754 (22%) were aged ≥70 years and 74% were screen detected. High grade DCIS was common, irrespective of age and method of presentation. Fewer women aged ≥70 had surgery compared to women aged 50–69 (81% vs. 94%), which was only partly explained by poor fitness. Use of radiotherapy following breast conserving surgery was strongly associated with grade, and was received by less than 16% of all patients with low grade tumours. Over 70% of women aged 50–69 with high grade DCIS received radiotherapy, but this fell to 35% among women aged ≥80. Use of radiotherapy was not associated with patient fitness. Conclusion: Treatment decisions for women with DCIS varied by age at diagnosis. Lower rates of surgery and adjuvant radiotherapy in older women were only partly explained by patient fitness. Better evidence is needed to aid treatment selection for older women with DCIS.